Desenvolvimento de sistema para gerenciamento de dados de pesquisa - Ferrasi, Emerson Carlos Sarti [UNESP] (Universidade Estadual Paulista (Unesp), 2013)
The biotechnological advances have contributed to the excellence in the quality of scientific research, as well as the exponential growth of data generated. The analysis and interpretation of data in scientific research is an essential activity when it seeks to generate biological knowledge of excellence. Information technology has emerged as an essential tool in data management and administrative processes. Public agencies funding have stimulated collaboration between research groups located in different institutions, often far apart geographically, enabled the creation of virtual research groups, where the exchange of information and discussion of results is done as efficiently as would be gathered in groups spot. It is common in scientific research, conducting various laboratory tests on a single sample, outlining projects with different approaches. However, by repeatedly such data, although they refer to the same sample, are not always analyzed together. This situation represents a loss of valuable biological information in the construction of scientific knowledge. In this context, it is important to develop computational tools for the storage and management of data generated in order to optimize the analysis of the results obtained over various scientific researches, but conducted in the same sample. This study aimed to develop a software for managing samples generated from research projects in the area of Health Sciences Development System had as its starting point the analysis of the data requirements necessary for development of a database, as well as the procedures for access to information. The researchers involved in scientific projects were consulted on the information model to manage. The system developed in this study can be considered an innovative tool in the area of Health Research as it is a software that evolves according to the needs of new research groups and obviate the need for intervention by IT professionals ...

Os avanços biotecnológicos vêm contribuindo para a excelência na qualidade das pesquisas científicas, bem como para o aumento exponencial dos dados gerados. A análise e interpretação dos dados obtidos em pesquisa científica é uma atividade essencial quando se busca gerar conhecimento biológico de excelência. A informática vem se destacando como uma ferramenta essencial no gerenciamento de dados e processos administrativos. Os órgãos públicos de financiamento têm estimulado a colaboração entre grupos de pesquisa situados em instituições diferentes, muitas vezes bem distantes geograficamente, possibilitado a criação de “grupos de pesquisa virtuais”, onde a troca de informações e discussão de resultados se faz de maneira tão eficiente quanto o seria em grupos reunidos in loco. É comum na pesquisa científica, a condução de diferentes análises laboratoriais em uma mesma casuística, delineando projetos com abordagens diferentes. Entretanto, por repetidas vezes, tais dados, embora sejam referentes à mesma casuística, nem sempre são analisados em conjunto. Tal situação representa perda de informações biológicas preciosas na construção do conhecimento científico. Nesse contexto, faz-se importante o desenvolvimento de ferramentas computacionais para o armazenamento e gerenciamento dos dados gerados, de forma a otimizar as análises dos resultados obtidos ao longo de pesquisas científicas diversas, porém conduzidas em uma mesma amostragem. O presente estudo teve como objetivo principal o desenvolvimento de um Software para o gerenciamento de amostras geradas a partir de Projetos de Pesquisa na Área de Ciências da Saúde. O desenvolvimento do Sistema teve como ponto de partida a análise de requisitos dos dados necessários para elaboração de um banco de dados, bem como os procedimentos de acesso às informações. Os pesquisadores envolvidos nos projetos científico foram consultados ...
Keywords: Banco de dados; Projeto de banco de dados; Pesquisa biomédica; Java (Linguagem de programação de computador); Biomedical research